Remote Origins: The Case of “Water Towns” of Olbicella and of Root *Alb- - Cacciafoco, Francesco Perono (2015)
Paleo-Ligurian place-names of the type Alba, Old European river names Albis and the like, as well as their ablauting forms Olb- (> Orb- in Romance Ligurian) do not reflect directly the proto-Indo-European adjective *albho-, 'white'; rather, they all continue a Pre-PIE extended root *Hal-bh-, 'water', cognate with Sumerian ḫalbia (>Akkadian ḫalpium, 'spring', 'well', 'water mass', 'water hole'). A further analysis of the same *Hal-bh- leads to a comparison with the PIE root *Hal-, 'nourish'. PIE suffixed form *HwaH-r-, 'water', exhibits a similar diffusion.